2017
DOI: 10.1111/zph.12435
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic origin and transmission of Middle East respiratory syndrome coronavirus in the UAE

Abstract: Since the emergence of Middle East respiratory syndrome coronavirus (MERS-CoV) in 2012, there have been a number of clusters of human-to-human transmission. These cases of human-to-human transmission involve close contact and have occurred primarily in healthcare settings, and they are suspected to result from repeated zoonotic introductions. In this study, we sequenced whole MERS-CoV genomes directly from respiratory samples collected from 23 confirmed MERS cases in the United Arab Emirates (UAE). These sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 52 publications
(70 reference statements)
2
59
0
Order By: Relevance
“…Despite moderate seropositivity, surveys have not detected active MERS-CoV infection in the dromedary populations of Bangladesh or Israel (David et al, 2018;Islam et al, 2018). RNA prevalence in dromedary populations linked to human cases was similar to more randomly sampled populations in the same country, with the exception of two small outbreak studies in the UAE which found 100% of epidemiologically linked dromedaries to be infected (Al Hammadi et al, 2015;Paden et al, 2018).…”
Section: Prevalence Of Active Mers-cov Infection -Cross-sectional Stumentioning
confidence: 93%
See 1 more Smart Citation
“…Despite moderate seropositivity, surveys have not detected active MERS-CoV infection in the dromedary populations of Bangladesh or Israel (David et al, 2018;Islam et al, 2018). RNA prevalence in dromedary populations linked to human cases was similar to more randomly sampled populations in the same country, with the exception of two small outbreak studies in the UAE which found 100% of epidemiologically linked dromedaries to be infected (Al Hammadi et al, 2015;Paden et al, 2018).…”
Section: Prevalence Of Active Mers-cov Infection -Cross-sectional Stumentioning
confidence: 93%
“…Our search found that dromedary populations in 16 countries have been tested for MERS-CoV RNA, 13 of which report positive results indicating active infection. These include KSA (0.12-56%) (Alagaili et al, 2014;Khalafalla et al, 2015;Sabir et al, 2016;Alfuwaires et al, 2017;Kasem et al, 2018a, b), UAE (0-29% (Wernery et al, 2015a, b;Yusof et al, 2015;Li et al, 2017;Yusof et al, 2017) or 0-100% if dromedaries epidemiologically linked to human MERS-CoV cases are included(Al Hammadi et al, 2015;Muhairi et al, 2016;Paden et al, 2018)), Qatar (22-79%) Reusken et al, 2014a;Farag et al, 2015;Mohran et al, 2016), Oman (7%) (Nowotny and Kolodziejek, 2014), Iraq (15%) (Al Salihi and Alrodhan, 2017), and Jordan (62%) (van Doremalen et al, 2017), as well as Egypt (4-15%) , Ali et al, 2017a, Ethiopia (10%) (Miguel et al, 2017), Kenya (0.35-0.95%) (Kiambi et al, 2018;Ommeh et al, 2018), Nigeria (3-11%) So et al, 2018), Burkina Faso (5%) (Miguel et al, 2017), Morocco (2%) (Miguel et al, 2017), and Pakistan (3%) . See Fig.…”
Section: Prevalence Of Active Mers-cov Infection -Cross-sectional Stumentioning
confidence: 99%
“…The Middle East respiratory syndrome (MERS) coronavirus first emerged in 2012 in Saudi Arabia (9). MERS-coronavirus also pertains to beta-coronavirus and having camels as a zoonotic source or primary host (18). In a recent study, MERS-coronavirus was also detected in Pipistrellus and Perimyotis bats (19), proffering that bats are the key host and transmitting medium of the virus (20,21).…”
Section: Primary Reservoirs and Hosts Of Coronavirusesmentioning
confidence: 99%
“…The emergence of dominant and recombinant MERS-CoV which caused a human outbreak in 2015 has been reported from camel [3]. The zoonotic introduction was suspected after the MERS-CoV identification [18] and in a recent study from UAE the genetic diversity of MERS-CoV full-genome from both human and dromedary camel was analyzed, and very closed sequence similarity was observed which confirms the zoonotic introductions [20,21]. Additionally, the zoonotic introduction time and seasons play an important role in the disease spread.…”
Section: Introductionmentioning
confidence: 93%